AB0309 Parathormone levels inversely correlate with clinical disease activity indexes in three severity subgroups of rheumatoid arthritis affected patients. (23rd January 2014) - Seriolo, B.; Meroni, M.; Paolino, S.; Zampogna, G.; Ferrone, C.; Alessandri, E.; Pizzorni, C.; Cutolo, M.
Abstract : Background: Rheumatoid arthritis (RA) is associated to an increased incidence of osteoporosis: more 15-20% at the standard measured sites. The main mechanisms leading to increased bone resorption in RA are the cytokines-induced osteoclastogenesis and parathyroid hormone (PTH) secretion impairment (1). Objectives: The aim of our study is to investigate if there is a correlation between PTH secretion levels, the Disease Activity Score on 28 joints (DAS28) and the Health Assessment Questionnaire-Disability Index (HAQ-DI) in a group of active RA patients. Furthermore it was investigated if the observed correlations vary according to the severity of the RA disease. Methods: We subsequently enrolled 81 RA patients diagnosed according to the 2010 ACR/EULAR criteria (2) and treated with DMARDs and low-dose glucocorticoids, excluding subjets treated with biological agents or calcium metabolism modifying drugs. After collection of patient informed consent and local Ethic Committee approval, we performed two visits where we collected blood samples and performed clinical evaluation. The patients were divided into three subgroups according to the disease activity range. DAS28 was calculated with C-Reactive Protein (CRP): DAS-28 score >5.1 indicates high disease activity (26 subjects); DAS28 score ≤3.2 low disease activity (27) and DAS-28 between 3.2 and 5.1 moderate disease activity (28) (3). HAQ-DI scores varies from 0 (no disability) to 3 (total disability) (4). PTH was measured as 1-84 fraction by chemiluminescence (DiaSorin Liaison®) and CRP by immunoturbidimetry (BioGamma LT006®). Baseline comparisons between patients scores and laboratory findings were performed with Student's t test for coupled data and Pearson χ 2 test. Results: Among high activity RA patients: DAS-28 vs PTH r=-0.40, p<0.05 (95% CI -0.68/-0.02); HAQ vs PTH r=-0.75 p<0.001 (95% CI -0.88/-0.52). Among patients with moderate disease activity subjects: DAS-28 vs PTH r= -0.91, p<0.0001 (95% CI -0.96/-0.84); HAQ vs PTH r=-0.92 p<0.001 (95% CI -0.98/-0.82). Finally, low disease activity patients showed: DAS-28 vs PTH r= -0.90, p<0.0001 (95% CI -0.95/-0.79); HAQ vs PTH r=-0.92 p<0.001 (95% CI -0.96/-0.82). Conclusions: Along with vitamin D, PTH exerts a modulatory role in bone resorption, but few is known about its fluctuations during RA relapses. In several papers (1, 5) its secretion seems inadequately low following hypocalcemic stimulus in RA patients: therefore, a disease-activity-dependent disturbance in PTH secretion cannot be excluded. We focused on PTH pathogenic role, founding that its levels are negatively related to the clinical RA activity parameters, with a clear statistical significance. The reduction in PTH serum levels contribute, along with vitamin D, to a low turnover state in bone remodeling, followed by a reduced osteoblasts activity that leads to an osteoporotic state in the presence of a chronic inflammatory noxia. For these reasons we believe PTH needing to be further investigated as a reliable marker of chronic inflammation-induced osteoporosis, likelihood in RA. References: Oelzner P et al. Rheumatol Int (2006)26:908-15. Arthritis Rheum (2010);62(9):2569-81. Vrijhoef HJM et al. Ann Rheum Dis (2003);62:419–422. Bruce B and Fries JF Clin Exp Rheumatol (2005);23(S39):S14-S18. Young N et al. J Immunol (2005);175:8287-95. Disclosure of Interest: None Declared